2017
DOI: 10.1186/s12917-017-1243-9
|View full text |Cite
|
Sign up to set email alerts
|

High intensity, short duration pulling in heavy horses: physiological effects of competition and rapid weight change

Abstract: BackgroundThe Heavy Horse Pull is a competition where teams of two horses pull an increasingly heavy sled for a short distance. Similar to human wrestlers, some horses may undergo rapid weight change in order to enter a lower weight category. The objectives were to study the physiological effects of this practice as well as of the pulling competition in draft horses.ResultsFifty horses were divided into light-, middle- and heavyweight categories based on their arrival weights and competed 1–3 days after. Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The level of total protein, albumin, globulin, creatinine and urea were found to be significantly increased. Greco-Otto et al, 2017 noticed that there was a strong correlation between plasma total protein, albumin, globulin, creatinine and urea. This increase in the values of these parameters was due to dehydration during intense work (Munoz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of total protein, albumin, globulin, creatinine and urea were found to be significantly increased. Greco-Otto et al, 2017 noticed that there was a strong correlation between plasma total protein, albumin, globulin, creatinine and urea. This increase in the values of these parameters was due to dehydration during intense work (Munoz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in ALT level after carrying more weight in these ponies addressed the question regarding the potential changes in ALT level post-exercise. It is reasonable to assume, that measurements of ALT levels might be reflected by load carrying programs in ponies at high altitude and impact on muscle mass because there is a strong correlation between AST and ALT, as well as between CK and ALT (Greco-Otto et al, 2017). Recently one of the study observed that low ALT blood activity, as a biomarker for increased weakness, is associated with lower baseline fitness of post-acute myocardial infarction and post-cardiac surgery patients going through a cardiac rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological indicators such as blood temperature ( 58 , 59 ), rectal temperature ( 39 , 42 , 46 , 60 , 61 ), heart rate ( 30 , 39 , 40 , 42 , 46 , 47 , 49 , 61 , 62 ), respiration rate ( 30 , 39 , 42 , 46 , 61 ), hematological profile ( 30 , 40 , 49 , 61 , 62 ), muscle fiber composition ( 39 , 40 , 63 ), creatinine kinase ( 62 , 64 , 65 ), lactate dehydrogenase ( 42 , 62 , 63 ), alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, citrate synthase, and 3-hydroxy acyl-CoA dehydrogenase ( 42 , 63 , 64 ), have been investigated in relation to the load pulling capabilities of equids ( Figure 5 ). However, the conditions under which this work has been done have been highly variable, so generalization of the results is difficult.…”
Section: Physiological Effects Of Loadingmentioning
confidence: 99%
“…However, this change in rectal temperature does not recover even after 1 h of rest after the end of exercise ( 46 ). This may be due to the faster metabolic rate in donkeys than horses ( 64 ), but this has yet to be investigated in relation to load pulling. These studies indicate that work speed may be more important than draught force in influencing body temperature, but a direct comparison between work speed and draught force in load pulling equids is never made.…”
Section: Physiological Effects Of Loadingmentioning
confidence: 99%
See 1 more Smart Citation